KONSELING INDIVIDUAL DENGAN TEKNIK COGNITIVE RESTRUCTURING UNTUK MENINGKATKAN RESILIENSI SISWA KELAS VIII SMPN 16 SURAKARTA TAHUN PELAJARAN 2025/2026 - Genta Buana, Tri Fosa; Ersta Kusumaningtyas, Lydia; Dwi Sholikhah, Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low academic resilience of Grade VIII students at SMP Negeri 16 Surakarta, attributed to broken home family conditions. The aim is to examine the effectiveness of individual counseling using the Cognitive Restructuring technique in improving students' academic resilience. A Guidance and Counseling Action Research (PTBK) design based on John Elliot's cyclical model was employed, consisting of two cycles with four stages each: planning, action, observation, and reflection. The research subject was a student (initials FP) with low academic resilience. Data were gathered through observation, interviews, documentation, and an academic resilience scale measuring confidence, control, composure, and commitment. Results demonstrated consistent improvement: observation scores increased from 57.02% (pre-cycle) to 71.87% (Cycle I) and 83.59% (Cycle II); scale scores rose from 46.35% to 70.83% and 82.03%. It is concluded that individual counseling with the Cognitive Restructuring technique effectively enhances academic resilience by transforming irrational thought patterns into rational and adaptive ones. Keywords: individual counseling; cognitive restructuring; academic resilience; junior high school students; broken home